Macrófagos associados ao tumor em carcinoma hepatocelular: avaliação quantitativa e correlação com aspectos clínicos e patológicos - Magalhães, Leila Carla da Cunha Silva (2010)
The role of macrophages in tumorigenesis is complex because they can both prevent and promote tumor development. The distinct microenvironments where tumor-associated macrophages (TAMs) act include intratumoral and peritumoral areas. This study aims to evaluate the evidence of TAMs´ infiltration in the tumoral microenvironment and its correlations with clinicopathologic features and prognostic values in resected hepatocellular carcinoma (HCC) patients.Methods:TAMs´ infiltration was evaluated in paraffin-embedded tissues from 35 HCC patients through immunohistochemistry methods. Each specimen was stained with the pan-monocyte/macrophage marker CD68, and average infiltration was quantitatively evaluated and results were expressed as cells-per-five-independent-visual-field by light microscopy (magnification, 400x). Correlation between TAMs´ infiltration and clinicopathologic features, were statistically analyzed. Results:Through the evaluation of these 35 specimens of hepatocellular carcinoma (HCC) we find a higher TAMs´ infiltration in the peritumoral area, which was statistically significant (p<0,001), regarding the intratumoral area. A second important result was a negative linear correlation between the presence of intratumoral TAMs and tumor size (p = 0.03).Conclusions:The tumor diameter is a recognized clinical prognostic factor in HCC, used worldwide. The negative correlation between tumor diameter and number of intratumoral TAMs reinforces the idea that the number of TAMs within the tumor may be a limiting factor for tumor growth in the microenvironment of HCC.